EKONOMI DAN KEKUATAN POLITIK - Harsasto, Priyatno (Faculty of Social and Political Sciences Diponegoro University, 2011)
Abstract :Â Economic growth in the emerging market is often followed by rent-seeking activities and corruption. Rent-seeking practice actually can happen everywhere; in advanced countries as well as in developing ones. However, rent-seeking activities in developing countries can be found in every activities. Korean experience is remarkably different. Rent-seeking activities and high economic performance can work together side by side.Key words: rent-seeking, mutual hostages, small groupspermalink:http://ejournal.undip.ac.id/index.php/forum/article/view/3154